O2-Tuned Protein Synthesis Machinery in Escherichia coli-Based Cell-Free System - Lin, Xiaomei; Zhou, Caijin; Zhu, Songbiao; Deng, Haiteng; Zhang, Jisong; Lu, Yuan (Frontiers in Bioengineering and Biotechnology, 2020)
Involved in most aerobic biochemical processes, oxygen affects cellular functions and organism behaviors. Protein synthesis, as the underlying biological process, is unavoidably affected by the regulation of oxygen delivery and utilization. Bypassing the cell wall, cell-free protein synthesis (CFPS) systems are well adopted for the precise oxygen regulation analysis of bioprocesses. Here a reliable flow platform was developed for measuring and analyzing the oxygen regulation on the protein synthesis processes by combining Escherichia coli-based cell-free protein synthesis systems and a tube-in-tube reactor. This platform allows protein synthesis reactions conducted in precisely controlled oxygen concentrations. For analysis of the intrinsic role of oxygen in protein synthesis, O2-tuned cell-free protein synthesis systems were explored with transcription-translation related parameters (transcripts, energy, reactive oxygen species, and proteomic pathway analysis). It was found that 2% of oxygen was the minimum requirement for protein synthesis. There was translation-related protein degradation in the high oxygen condition leading to a reduction. By combining the precise gas level controlling and open biosystems, this platform is also potential for fundamental understanding and clinical applications by diverse gas regulation in biological processes.